The distribution of Streptococcus mutans and Streptococcus sobrinus in children with dental caries severity level - Nur Dianawati; Wahyu Setyarini; Ira Widjiastuti; Rini Devijanti Ridwan; K. Kuntaman (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: The prevalence of dental caries is high worldwide and specifically in Indonesia, especially in children. Cariogenic bacteria are the major cause of dental caries. Streptococcus mutans (S. mutans) is one of the bacteria often associated with caries, due to its ability in producing acid and forming the biofilm for bacterial colonisation on the surface of oral cavities. In addition to S. mutans, Streptococcus sobrinus (S. sobrinus) bacteria are also thought to play an important role in the process of caries. Purpose: This study aims to analyse the distribution of S. mutans and S. sobrinus in children with seriously high dental caries levels. Methods: This study was an observational analytical study. Bacterial isolation was conducted in carious lesions of 50 paediatric patients 6-12 years old with superficial dental caries. Samples of caries lesions were put directly into a tube containing the Brain Heart Infusion Broth (BHI-B) and incubated at 37o C for 24 hours. The samples were sub-cultured on selective tryptone yeast cystine sucrose bacitracin (TYCSBHimedia) agar, and then incubated for two days. Bacterial identification was then performed using the polymerase chain reaction (PCR) Multiplex method. Statistical analysis with Chi-square. Results: The total number of children with dental caries included in this study was 50. Among these, 94% showed positive for S. mutans and 30% positive for S. sobrinus. The analysis of the prevalence of bacterial colonisation (S. mutans and S. sobrinus) based on caries severity and the Simplified Oral Hygiene Index (OHI-S), showed there was no significant difference (p> 0.05). Conclusion: This study showed that among 50 caries noted in the children, 94% were colonised S. mutans and 30% S. sobrinus. There was no significant difference between the colonisation of S. mutans and S. sobrinus among children from the severe to mild decayed exfoliated filling teeth (DEFT) category, and between bad and good OHI-S.